ASME 2010 Summer Bioengineering Conference, Parts a and B 2010
DOI: 10.1115/sbc2010-19583
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulated Bone Remodeling May Explain Bone Structural Changes Observed in Osteoarthritis

Abstract: Osteoarthritis (OA) affects both the articular cartilage and the subchondral bone. It is a complicated disease, associated with conditions varying from obesity and strenuous exercise to joint malalignment, anterior cruciate ligament (ACL) injury, and even metabolic bone diseases. Patients suffer from chronic joint pain and limitation of motion, and no cure is yet available. For many years, medical therapies have been focused on cartilage, because bone changes were thought not to play a major role in the OA dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, bone structural changes seemed correlated with the degree of degeneration of the overlying cartilage [3]. Previously, we showed that mechanoregulated bone adaptation probably remains intact in OA [4]. Therefore, we hypothesize that the decrease in matrix mineralization observed in OA is related to the degeneration of the cartilage, and that this decrease in mineralization in turn causes subchondral bone structural changes, through mechanoregulated bone adaptation.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, bone structural changes seemed correlated with the degree of degeneration of the overlying cartilage [3]. Previously, we showed that mechanoregulated bone adaptation probably remains intact in OA [4]. Therefore, we hypothesize that the decrease in matrix mineralization observed in OA is related to the degeneration of the cartilage, and that this decrease in mineralization in turn causes subchondral bone structural changes, through mechanoregulated bone adaptation.…”
Section: Introductionmentioning
confidence: 90%